PENERAPAN MODEL INKUIRI UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA PADA MATERI GAYA DAPAT MEMPENGARUHI GERAK BENDA - Hendrawan, Ruhiat; Jayadinata, Asep Kurnia; Hanifah, Nurdinah (Jurnal Pena Ilmiah, 2017)
This research is motivated by the low motivation of students in science learning on the material style can influence the motion of objects, so that the student learning outcomes become low. So it needs an effort to fix the problem. One attempt to improve it is to apply the inquiry learning model. This study aims to find out how the picture of inquiry learning model to improve students' motivation and learning outcomes, on the material style can affect the motion of objects. The subjects of this study were 22 students of grade IV B SD Negeri Padasuka 1, Kec. North Sumedang, Kab. Sumedang. This research has succeeded in improving motivation and student learning outcomes on the material style can influence the motion of objects in class IV B SD Negeri Padasuka 1. This can be seen motivation and student learning outcomes from continuously increases in each cycle.